155k views
3 votes
If x² + y² = 7xy prove that
log(xty) - log3 + 1/2 log×+logy​

1 Answer

0 votes

Answer:

n = m

By the definition of logarithms and due to the fact that logarithms are...

Explanation:

Now, by the “logarithm of a power” property, we have:

log (x + y)² = log (xy) – log 3²

log (x + y)² = log (xy) – log 9

Now, by the “logarithm of a quotient” property, we have:

log (x + y)² = log (xy/9)

Now, let n = log (x + y)² and m = log (xy/9), then, substituting, we have the equality:

n = m

User Rocket
by
5.1k points